أثر تطبيق الضريبة الانتقائية على السجائر في زيادة الحصيلة الضريبية: The effect of applying the selective tax on cigarettes on increasing the tax revenue (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The increasing rates of consumption of cigarettes harmful, to health in the world in general, and in Iraq in particular, and because of the costs borne by individuals, and the state as a result of addressing its damage, as well as Iraq's commitment, to international conventions against cigarettes, and demands of the World Health Organization, to raise prices to reduce consumption. Therefore, the tax Selectivity is one of the most important ways of regulating the consumption of this commodity on the one hand and increasing the tax revenue on the other. The research aims to shed light on the issue of selective tax on cigarettes and the impact of their application in increasing tax revenues and identify the effectiveness of the application of this tax in the Iraqi environment through the development of a proposed framework on the law of selective tax. Based on the hypothesis of the research that the application of the method of selective tax on cigarettes in the Iraqi work environment in increasing tax revenue, the research concluded with a set of conclusions and recommendations, including that the selective tax several advantages, the most important of which is the heavy outcome and monthly collection, so it is a good resource in increasing the proceeds Taxation, as well as the legalization of consumption of harmful goods by consumers and the most important recommendations reached is the legislation of a law on selective tax and through the use of the experiences of some of the countries applying them.